Current advances on school refusal and other attendance problems: An international perspective. Introduction to the Special Issue. (European Journal of Education and Psychology, 2019)
Current advances on school refusal and other attendance problems: An international perspective. Introduction to the Special Issue. The school attendance problems affect a larger number of students worldwide than desired. Important negative effects on academic, social and personal development are associated with this phenomenon. The aim of this special issue is to present the most recent advances in this field of research from an international perspective. For this, this special series has six investigations framed in the context of Spain, France, the United States, Japan, Malaysia and the Netherlands. Among the main contributions, the works compiled here have managed to reflect on the school refusal behavior reaching three levels of analysis: (1) legal and political level, (2) personal level of the child or young person affected and (3) family level. Based on the findings obtained, it is concluded that promoting prevention and reducing the school attendance problems are activities that have no limits geographically. It is a purpose shared by all the studies that make up this special issue to encourage reflection and promoting new lines of research.